A perspective on psychological factors affecting the emotional labor of teachers - Attwood, Adam I. (Frontiers in Education, 2024)
Several psychological factors are discussed in relation to teachers’ emotional labor (EL). Ecological systems theory (EST) is used in relation to the role of emotional intelligence (EI) to provide a perspective on ways to conceptualize how to address secondary traumatic stress (STS) risk among teachers. An international selection of the literature is synthesized in relation to the factors that may affect EL in relation to STS risk among teachers who have students with adverse childhood experiences (ACEs). The concept of EI is central to this discussion of theoretical relationships between EI and STS risk relevant to teachers’ EL. While there is much literature on Bronfenbrenner’s EST and Gardner’s multiple intelligences (MI) theory separately, there is room in the literature for exploring EST to contextualize the topic of STS risk as it relates to the concept of EI. The purpose of this study is to discuss allostatic load factors that may affect teachers’ EL and to discuss potential ways to acknowledge EL.